ADP-ribosylation factor–like 4C binding to filamin-A modulates filopodium formation and cell migration - Chiang, Tsai-Shin; Wu, Hsu-Feng; Lee, Fang-Jen S. (Molecular biology of the cell, 2017)
Changes in cell morphology and the physical forces that occur during migration are generated by a dynamic filamentous actin cytoskeleton. The ADP-ribosylation factor–like 4C (Arl4C) small GTPase acts as a molecular switch to regulate morphological changes and cell migration, although the mechanism by which this occurs remains unclear. Here we report that Arl4C functions with the actin regulator filamin-A (FLNa) to modulate filopodium formation and cell migration. We found that Arl4C interacted with FLNa in a GTP-dependent manner and that FLNa IgG repeat 22 is both required and sufficient for this interaction. We also show that interaction between FLNa and Arl4C is essential for Arl4C-induced filopodium formation and increases the association of FLNa with Cdc42-GEF FGD6, promoting cell division cycle 42 (Cdc42) GTPase activation. Thus our study revealed a novel mechanism, whereby filopodium formation and cell migration are regulated through the Arl4C-FLNa–mediated activation of Cdc42.